Ratio of cord blood bilirubin and albumin as predictors of neonatal hyperbilirubinaemia - Sharma, Indra Kumar (Clin Exp Hepatol, 2020)
AIM OF THE STUDY: To compare cord blood albumin (CBA) and cord blood bilirubin (CBB) at birth as predictors for development of neonatal hyperbilirubinaemia. MATERIAL AND METHODS: CBA and CBB of 388 healthy term neonates born by lower segment caesarean section (LSCS) were determined at birth and transcutaneous bilirubin (TCB) was measured every 12 hours from birth until 7 days of life or development of hyperbilirubinaemia requiring phototherapy. RESULTS: The cut-off value of CBB and CBA as obtained by the receiver operating characteristic (ROC) curve was 1.90 mg/dl and 3.17 g/dl respectively. The sensitivity, specificity and positive predictive value (PPV) for CBB were 97.4%, 40.6% and 71.09% while for CBA they were 40.8%, 34.8% and 48.41%. The cut-off value for CBB/CBA ratio was 0.719 as obtained by the ROC curve and was determined to have 97.4% sensitivity, 62.6% specificity and a PPV of 79.61%. CONCLUSIONS: CBB/CBA is a better indicator compared to CBA and CBB alone for prediction of neonatal hyperbilirubinaemia.